DIGITAL BANKING STRATEGY ANALYSIS OF BRI - Lieza Muliasari (Jurnal Ekonomi, 2022)
Digital technology is becoming a concern and trend in the banking and financial services industries. Competing in the banking business requires mastery and adaptability to the most recent technical innovations. Technology is used to increase the effectiveness and efficiency of the company's operational operations, as well as to enhance service quality in order to sustain client relationships. The banking sector must expedite the introduction of digital banking in order to remain competitive by providing simpler and quicker services and meeting client demands.This research intends to assess Bank Rakyat Indonesia's digital banking strategy. As one of the largest banks in Indonesia, Bank BRI is digitally transforming its business operations with the use of technology-based goods and services, as well as improvements to the company's work culture. The study involves both internal and external development. Using the Technology Adoption Model, the author evaluates the acceptance of digital technology by users of the BRI Mobile application. The author employs a mixed qualitative and quantitative research approach with a focus on the qualitative components of this study.The author determined, based on the notion of Digital Banking, that BRI had developed a strong digital banking strategy. BRI created services and products that give customers with novel experiences and an efficient operational approach. In the examination of technology adoption of BRI Mobile users, perceived utility and perceived simplicity of use had a favorable influence on behavioral intention